Inventory of timber and non-timber forest products through remote sensing and mapping: The example of bamboo resources in chad - Tchoutezou Guy Herman Zanguim; Tanougong Nkondjoua Armand Delanot; René Kaam; Henry Ouya Bondoro; Ngoh-Allah Odjimbaye; Nyong Princely Awazi; Martin Ngankam Tchamba (Advances in Bamboo Science)
This study was initiated to explore the potential of the bamboo resource in Chad, a vital component for socio-economic development, environmental protection and biodiversity conservation. Inspired by proven methodologies in Ethiopia, Kenya, Uganda and Madagascar, our research mapped and inventoried Chad's bamboo resources using advanced remote sensing techniques. A series of multi-temporal Landsat images with a spatial resolution of 30 m were used. Almost 90 Landsat 8 OLI image sheets were assembled into a mosaic using Envi 5.3 software. Careful processing, including pre- and post-classification, was applied to refine the mapping. Validation of the presence of bamboo was carried out using GPS coordinates and very high spatial resolution images, such as those provided by Google Earth. The overall accuracy of the study was evaluated at 87.85 %, with a Kappa coefficient of 0.83, attesting to the reliability of the results obtained. Bamboos are present in three distinct climatic zones of the country: the Guinean, Sudanian and Sahelian zones. They cover a total area of around 35,600 ha, with a distribution of 21 % in the Sahelian zone and 79 % in the Sudanian zone, implying no traces of bamboo were found in the Guinean zone. Oxythenanthera abyssinica (A.Rich.) Munro was the only bamboo species identified on the territory, underlining its predominant ecological role and its adaptation to Chad's diverse environments. Although bamboo is not abundant in Chad, its importance cannot be overemphasized. Bamboo makes a significant contribution to the fight against climate change, thanks to its capacity to sequester carbon and its role in soil stabilization. These characteristics make bamboo a strategic resource in efforts to combat desertification. The results of our study provide a sound basis for the sustainable management of bamboo resources in Chad. Our findings call for the development of policies aimed at reducing rural poverty and integrating bamboo management into systems for combating desertification. We recommend that bamboo research and development programs be pursued in order to maximize its economic potential while preserving its ecological integrity. We therefore highlight the crucial role of bamboo in Chadian ecosystems and its untapped potential as a resource for sustainable development. Implementing the recommendations arising from our research will significantly transform Chad's socio-economic and environmental landscape, making bamboo a pillar of green growth and climate resilience.